DISPARITIES IN HEALTHY LIFE EXPECTANCY: THE ROLE OF PLACE, PERSON AND TIME. (11th November 2018) - Jagger, C; Robine, J
Abstract: A key concern for most countries is whether the added years of the longer lives now experienced are healthy and good quality years. Population health indicators such as healthy life expectancy, or the European indicator Healthy Life Years (HLY), that combine information on mortality and morbidity, are growing in importance, as they provide evidence to answer such concerns. Countries are also increasingly utilising these indicators to indicate and monitor the extent to which longer healthier lives are being enjoyed by all sections of the population, as defined by personal characteristics (education, socio-economic status) or place of residence. In this session we present new research on healthy life expectancy disparities within four countries (US, UK, Mexico, France) and explore the underlying drivers that can point towards solutions to reduce future disparities. The first presentation documents rural-urban differences in cognitive life expectancies at age 50 for Mexico and how personal characteristics (gender, education) contribute. The second presentation moves to regional variation in healthy and unhealthy life years across the 100 counties (departments) in France and examines, through meta-regression, the extent to which this variation is associated with disparities in local socio-economic context and long term care provision. In the third presentation US state differences in HLE are examined in light of state differences in socioeconomic and policy contexts. The final presentation focuses on person and time by looking to the future and examining the different ways in which dependency-free in England will evolve over the coming 20 years for men and women.